Contrasting Adult and Emerging Adult Women on Possible Psychosocial and Behavioral Correlates of Short-Term Weight Loss - James J. Annesi; Ping H. Johnson (New Prairie Press, 2019)
Physical activity could be associated with psychosocial correlates of changes in eating behaviors required for weight loss. This field investigation assessed relationships of physical activity with early changes in psychosocial variables such as depression, fatigue, and body satisfaction; and their effect on fruit/vegetable and sweets intake and weight change. Emerging adult women from a university setting (Mage = 20.4 years, SD = 2.0; n = 36) and adult women from a community health-promotion setting (Mage = 45.6 years, SD = 7.3; n = 36), participating in the same cognitive-behavioral weight-loss program that initiated physical activity prior to nutrition changes, were first contrasted on measures of physical activity, psychosocial changes, eating changes, and weight; then on their theory-based interrelations. The emerging adult women had significantly higher baseline scores on depression and physical activity, and significantly lower scores on fruit/vegetable intake. Improvements over 3 months in the psychosocial and behavioral variables and weight were significant, but did not significantly differ by group. Weight loss means were -3.89 kg and -4.16 kg, respectively. Using aggregated data, serial mediation analyses identified a significant path from change in physical activity, to change in depression, to change in intake of sweets, to change in weight. Paths were also significant when improvement in tension and fatigue was entered as the psychosocial variable. Age group did not moderate those relationships. Findings improved understandings of age effects, and interrelations of psychosocial and behavioral predictors of short-term weight loss that could help longer-term treatment targets.